Development of a rice-based chocolate beverage - Canadella, Christopher Patio ; Ma. Leonora dL Francisco, adviser (2005)
ABSTRACT The most acceptable levels of rice flour and stabilizer to be used in the production of the rice-based chocolate beverage were determined. Rice flour from AKG Grains Product was used at different amounts (4%, 10% and 30%) as base for the beverage production. κ-carrageenan (Hygel DS), on the other hand, was used as stabilizer at different concentrations (0.08%, 0.15%, and 0.20%) to determine the most effective level of stabilizer that will produce the most stable product. The basis for determining the most acceptable level of rice flour was viscosity acceptability. 4% rice flour was used in the production of the rice-based chocolate beverage since it provided high viscosity acceptability and the least viscous rice base among prepared mixtures. The effectivity of κ-carrageenan, in contrast, was measured based on its ability to increase the visual stability index as well as the consumer acceptance of the drink. Results showed that 0.15% κ-carrageenan was the most acceptable level for the rice-based chocolate beverage production and gave 0.97 visual stability index upon standardization.